High‐Sensitivity Acoustic Molecular Sensors Based on Large‐Area, Spray‐Coated 2D Covalent Organic Frameworks. Issue 42 (16th September 2020) - Evans, Austin M.; Bradshaw, Nathan P.; Litchfield, Brian; Strauss, Michael J.; Seckman, Bethany; Ryder, Matthew R.; Castano, Ioannina; Gilmore, Christopher; Gianneschi, Nathan C.; Mulzer, Catherine R.; Hersam, Mark C.; Dichtel, William R.
Abstract: 2D covalent organic frameworks (2D COFs) are a unique materials platform that combines covalent connectivity, structural regularity, and molecularly precise porosity. However, 2D COFs typically form insoluble aggregates, thus limiting their processing via additive manufacturing techniques. In this work, colloidal suspensions of boronate‐ester‐linked 2D COFs are used as a spray‐coating ink to produce large‐area 2D COF thin films. This method is synthetically general, with five different 2D COFs prepared as colloidal inks and subsequently spray‐coated onto a diverse range of substrates. Moreover, this approach enables the deposition of multiple 2D COF materials simultaneously, which is not possible by polymerizing COFs on substrates directly. When combined with stencil masks, spray‐coated 2D COFs are rapidly deposited as thin films larger than 200 cm 2 with line resolutions below 50 µm. To demonstrate that this deposition scheme preserves the desirable attributes of 2D COFs, spray‐coated 2D COF thin films are incorporated as the active material in acoustic sensors. These 2D‐COF‐based sensors have a 10 ppb limit‐of‐quantification for trimethylamine, which places them among the most sensitive sensors for meat and seafood spoilage. Overall, this work establishes a scalable additive manufacturing technique that enables the integration of 2D COFs into thin‐film device architectures. Abstract : High‐resolution, large‐scale fabrication of 2D covalent organic framework (COF) thin films is achieved by spray‐coating colloidal inks of these materials. Using this additive manufacturing approach, 2D COF thin films are integrated into acoustic sensing platforms. These sensors achieve superlative detection of volatile amines including a limit‐of‐quantification of 10 ppb for trimethylamine, which is a target analyte for the detection of food spoilage.